Access to institutional delivery services and its associated factors among mothers in Jimma Zone, Southwest Ethiopia: a cross-sectional study - Kayrite, Qaro Qanche (BMC Public Health, 2020)
BACKGROUND: Poor access to institutional delivery services has been known as a significant contributory factor to adverse maternal as well as newborn outcomes. Previous studies measured access in terms of utilization while it has different dimensions (geographic accessibility, availability, affordability, and acceptability) that requires to be measured separately. Therefore, this study was conducted to assess the four dimensions of access and factors associated with each of these dimensions. METHODS: Community-based cross-sectional study design was used, employing both quantitative and qualitative methods. A simple random sampling technique was used to select 605 mothers who had given birth in the last 6 months preceding the study. Multi-variable binary logistic regression was used to select factors associated with the four dimensions of access by using AOR with 95% CI. Ethical approval was secured from Jimma University Institutional Review Board. RESULTS: Five hundred and ninety-three mothers involved in this study, resulting in a response rate of 98%. Four hundred five (68%), 273(46%), 279(47%), and 273(46%) had geographic, perceived availability, affordability, and acceptability access to institutional delivery services, respectively. Antenatal care [AOR = 3.74(1.56, 8.98)], occupation of mother [AOR = 5.10(1.63, 15.88)], and residence [AOR = 1.93(1.13, 3.29)] were independently associated with geographic accessibility. Household graduation [AOR = 1.46(1.03, 2.06)], residence [AOR = 1.74(1.17, 2.59)], and ANC [AOR = 3.80(1.38, 10.50)] were independently associated with perceived availability. Moreover, wealth quintile [AOR = 11.60(6.02, 22.35)], ANC [AOR = 3.48(1.36, 9.61)], and occupation of husband [AOR = 3.63(1.51, 8.74)] were independently associated with affordability. Lastly, mother’s education [AOR = 2.69(1.42, 5.09)], residence [AOR = 2.60(1.66, 4.08)], and household graduation [AOR = 3.12(2.16, 4.50)] were independently associated with acceptability of institutional delivery services. CONCLUSIONS: Moderate proportions of mothers have geographic accessibility to institutional delivery services, but access to the other three dimensions was low. ANC visits of 4 or above, occupation of husband, urban residence, graduation of mother’s household as a model family, higher wealth quintiles, and maternal educational level significantly affect access to institutional delivery services. Thus, it was recommended that concerned bodies should give due attention to ANC services, female education, training of model families, and enhancement of household wealth through job creation opportunities to increase access to institutional delivery services.